Pemanfaatan Digital Marketing untuk Meningkatkan Potensi Wisata Kampung Gambut Siantan Hilir - Amanda, Zhakia Putri; Wendy, Wendy; Rosari, Carviena Alia; Novita, Nanda; Oviska, Astrid; Ningsih, Welly Putri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This study investigated the development of identity and promotional strategies for tourism in Kampung Gambut Siantan Hilir, aiming to enhance local tourism awareness among residents of Pontianak city. A significant challenge identified is the insufficient information and promotional efforts regarding local tourism, particularly among urban populations unaware of nearby attractions, such as “vegetable picking”, located just a few kilometers from the city center. The research employs sosial media and visual content as primary tools for disseminating information about Kampung Gambut’s attractions. Additionally, the creation of informative tour packages, visual booklets, and brochures seeks to broaden public understanding of various available tourism offerings. Methodological approaches include developing engaging content, strategically planning educational tour packages, and producing unique merchandise that reflects the village’s positive image. The involvement of local communities in promotional activities is emphasized to enhance engagement and participation. Findings indicate that targeted promotion through sosial media and visual content effectively highlights tourism potential, while merchandise plays a crucial role in positioning Kampung Gambut Siantan Hilir as an appealing educational tourism destination, ultimately fostering increased community visit and participation.